2019
DOI: 10.1158/1078-0432.ccr-19-1305
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/Ib Study of Pembrolizumab Plus Vorinostat in Advanced/Metastatic Non–Small Cell Lung Cancer

Abstract: Purpose: Histone deacetylase inhibitors (HDACi) enhance tumor immunogenicity through several mechanisms and may improve response to immune checkpoint inhibitors (ICIs). In a phase 1/1b trial, we tested the oral HDACi vorinostat combined with the programmed cell death protein 1 inhibitor pembrolizumab in advanced/metastatic non-small cell lung cancer (NSCLC).Experimental Design: Patients received intravenous pembrolizumab (200 mg every 3 weeks) plus oral vorinostat (200 or 400 mg/day). Primary endpoint was safe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…Given that the HDAC inhibitor (HDACi) pembrolizumab is currently in clinical trials for use in lung cancer patients (35), our findings will be helpful to establish clinical study protocols. What is more, our results suggested that HDAC is might act on the immune networks of lung cancer cells, including changes in the profiles of co-stimulatory molecules, costimulatory antigens and cytokines of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the HDAC inhibitor (HDACi) pembrolizumab is currently in clinical trials for use in lung cancer patients (35), our findings will be helpful to establish clinical study protocols. What is more, our results suggested that HDAC is might act on the immune networks of lung cancer cells, including changes in the profiles of co-stimulatory molecules, costimulatory antigens and cytokines of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…No significant correlation was found between peripheral blood MDSCs and response rates upon treatment, probably because of the small sample number. Patients with NSCLC showed higher levels of MDSCs than heathy donors [ 238 ].…”
Section: Combination Strategiesmentioning
confidence: 99%
“…Due to the relevance of HDAC/HAT pathways in regulating the immune system, HDACis have been considered as immunomodulatory agents (Banik et al, 2019), thus they have been combined with ICIs. Pembrolizumab (an anti-PD1 inhibitor) with vorinostat was well-tolerated in advanced/metastatic non-small cell lung cancer and anti-tumor activity was demonstrated (Gray et al, 2019). Another combination strategy is the use of antibodies, anti-PD-1 or anti-CTLA-4.…”
Section: Pan-hdacis In Combination With Immunotherapymentioning
confidence: 99%